The Effectiveness of Metasteps-Based Virtual Biodiversity Learning in Improving Students’ Critical Thinking Skills - Nur Faridah; Ulfa Zahrani; Bambang Supriatno; Yanti Hamdiyati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
The widespread integration of digital technology into biology education has created a pressing need for learning platforms that simultaneously engage students and cultivate higher-order thinking skills. Despite the growing adoption of virtual environments and discovery-based learning models, empirical evidence examining their combined pedagogical effect on critical thinking within biodiversity topics remains scarce. This study aimed to evaluate the effectiveness of Metasteps-Based Virtual Biodiversity Learning in improving 10th-grade students' critical thinking skills regarding biodiversity threats and conservation efforts. A pre-experimental approach was employed using a one-group pretest-posttest design, involving 36 tenth-grade students at a private high school in Bandung Regency during the 2025/2026 academic year. The primary instrument was a 15-item multiple-choice critical-thinking test developed based on Facione’s indicators, encompassing interpretation, analysis, inference, evaluation, explanation, and self-regulation. Data normality was assessed using the Shapiro–Wilk test; because both pretest and posttest scores were non-normally distributed (p < 0.05), the Wilcoxon Signed-Rank Test was applied as the inferential statistical procedure. Effect size was calculated using the formula r = Z divided by the square root of N to quantify the practical significance of the intervention. Results revealed a statistically significant improvement in critical thinking skills from pretest to posttest (Z = –4.729; p < 0.001), with an effect size of 0.78, classified as moderate according to Cohen’s criteria. Indicator-level analysis showed gains across all six dimensions, with the largest improvements observed in analysis and explanation (23 percentage points each). These findings indicate that integrating a three-dimensional virtual biodiversity environment with structured stages of discovery learning can yield meaningful gains in students’ critical thinking. The study provides practical evidence for the use of immersive virtual platforms as an alternative science-learning strategy aligned with 21st-century educational demands.